2010
DOI: 10.4103/0019-5413.62051
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic lumbar discectomy: Experience of first 100 cases

Abstract: Background:Various modalities of treatment from standard discectomy, microdiscectomy, percutaneous discectomy, and transforaminal endoscopic discectomy have been in use for lumbar intervertebral disc prolapse. The access to spine is kept to a minimum without stripping paraspinal muscles minimizing muscle damage by posterior interlaminar endoscopic approach. The aim of this study was to evaluate technical problems, complications, and overall initial results of microendoscopic discectomy.Materials and Methods:Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 31 publications
4
57
0
1
Order By: Relevance
“…Manual review of the reference sections of included studies yielded eight additional publications that met inclusion criteria and were included in this review. Thus, a total of 15 articles were included in our systematic review, none of which were case reports [1,3,6,8,11,12,15,16,18,19,21,[23][24][25]27] (Table 1).…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…Manual review of the reference sections of included studies yielded eight additional publications that met inclusion criteria and were included in this review. Thus, a total of 15 articles were included in our systematic review, none of which were case reports [1,3,6,8,11,12,15,16,18,19,21,[23][24][25]27] (Table 1).…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…We included nine publications with Level IV evidence (case series without comparison group) [3,6,12,15,16,21,23,24,27], four with Level III evidence (retrospective comparative study) [1,8,11,18], and two with Level II evidence (prospective comparative study) [19,25].…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Open discectomy was considered as the gold standard for the treatment of lumbar disc prolapse by many authors 9,35 , and the majority of series 2,6,12,[14][15][16]18,36,42,44,45,47,48,51 reported satisfactory results in 75 to 95% of patients. Though the results of conventional discectomy are equally good, microdiscectomy introduced by Yasargil and Caspar (1977) is now considered the gold standard.…”
Section: Introductionmentioning
confidence: 99%